2020
DOI: 10.1055/s-0040-1707133
|View full text |Cite
|
Sign up to set email alerts
|

Amide Synthesis by Transamidation of Primary Carboxamides

Abstract: The amide functionality is one of the most important and widely used groups in nature and in medicinal and industrial chemistry. Because of its importance and as the actual synthetic methods suffer from major drawbacks, such as the use of a stoichiometric amount of an activating agent, epimerization and low atom economy, the development of new and efficient amide bond forming reactions is needed. A number of greener and more effective strategies have been studied and developed. The transamidation of primary am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This is because amides are much more stable than other acylating reagents such as acid chlorides, anhydrides, and esters. It has been reported that amides bearing various N -substituents were employed and reacted with amines to afford the desired transamidated products under the conditions with 4 or without transition metal catalyst. 5 Reactions of nitrogen-, carbon-, oxygen-, and sulfur-based nucleophiles with amides have been described.…”
Section: Introductionmentioning
confidence: 99%
“…This is because amides are much more stable than other acylating reagents such as acid chlorides, anhydrides, and esters. It has been reported that amides bearing various N -substituents were employed and reacted with amines to afford the desired transamidated products under the conditions with 4 or without transition metal catalyst. 5 Reactions of nitrogen-, carbon-, oxygen-, and sulfur-based nucleophiles with amides have been described.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23] As one of the oldest approaches, amide bond formation via mixed anhydride has been widely applied on the plant scale, 8 including amine condensation with anilines. [24][25][26][27] In the presence of a base, namely Et 3 N, NMM or N-methylpiperidine, carboxylic acids are first transformed into the corresponding mixed anhydrides using acid chlorides, such as pivaloyl chloride (PivCl) [28][29][30][31][32][33][34][35][36][37][38][39][40][41] or isobutyl chloroformate (IBCF). [42][43][44][45][46][47][48][49][50][51] The advantages of PivCl for scale-up include its relatively low cost, wide availability, and nontoxic pivalic acid as a byproduct after aqueous workup.…”
Section: Introductionmentioning
confidence: 99%
“…Although, transamidation is very well documented with planar and resonance stabilized unactivated primary amides. 28 Nevertheless, it has at least one or more of the following shortcomings: it requires heavy metal catalysts, additives, peroxide activators, strong bases, microwave irradiation, a long reaction time, and an inert atmosphere or it is limited to primary amides, with limited substrate scope, formylation/acetylation, low yields, high reaction temperature, and excessive use of additive/reagents. However, in the present work, a simple N -pivaloyl activation overcomes the above limitations.…”
Section: Introductionmentioning
confidence: 99%